Digital transformation and sustainable development: Empowering emerging Islamic economies through the creative economy - Fajar Juanda Matroji (Journal of Islamic Economic Insights, 2025)
This literature review investigates the intersection of digital transformation, sustainable development, and the creative economy in emerging Islamic economies. It explores how digital transformation can foster economic empowerment and sustainable development within Islamic finance. Integration of digital technologies in finance, commerce, and public services promises inclusive growth and efficiency. The review also examines the creative economy's role in fostering innovation, resilience, and societal development. Furthermore, it discusses incorporating Sustainable Development Goals into the Islamic economy, aligning principles of social justice, ethical conduct, and sustainability. Embracing SDGs, Islamic economies aim to eradicate poverty, promote gender equality, and ensure sustainable industrialization. The review highlights the creative economy's role in socio-economic development, job creation, and cultural preservation in Islamic economies. It offers insights and recommendations for policymakers, industry leaders, and stakeholders to advance digital transformation, sustainable development, and economic prosperity in emerging Islamic economies.